The effect of Shahnameh reading on aggression, social skills and national identity of students - Tanha, Zahra; Momeni Mofrad, Masoome; Nasiri Zade, Masoome (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Iran is a country with valuable cultural and artistic works and Ferdowsi Shahnameh is one of them. Unfortunately, despite the existence of such a valuable treasure and the exploits that can be made of it, especially in education, it has been used to a limited extent. Accordingly, this study sought to investigate the effect of holding Shahnameh reading courses on aggression, social skills and national identity of students. Methods: This study is based on the applied purpose and in terms of the type of research in the field of quasi-experimental studies. The statistical population of this study consists of all fourth-grade students of girls’ schools in Khorramabad. Sampling in this study was performed using the available non-probability method. Accordingly, after conducting initial discussions and obtaining permission from the students’ parents, finally 30 people from the statistical community were identified as the research sample. The data required in this study were collected using a questionnaire based on a 5-point Likert scale. Aggression was assessed using the AGQ questionnaire with 30 questions, social skills were assessed using the Gersham and Elliott (1990) questionnaire with 29 items, and national identity was assessed based on the Batman questionnaire (2005) with 12 items. The data collected in this study were analyzed due to the non-normality of the obtained data using Wilcoxon test. Results: Findings of this study showed that the average aggression of students after holding the Shahnameh reading course decreased significantly (with a significant level of 0.000) to 0.827. Descriptive analysis of the data shows that the average of social skills and national identity increased by 0.648 and 0.758, respectively, at the significant level of 0.002 and 0.001. Conclusion: The results of this study show a Z statistic above 1.96 for each of the variables, which shows a significant difference between the means before and after the Shahnameh reading period.